(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
Labour welfare as the work for improving the health, safety, general wellbeing and industrial efficiency of the workers beyond the minimum standards lay down by various Acts and Legislations. International Labour Organization (ILO) defined Labour Welfare as “Workers” welfare, such as services facilities and amenities which may be established on or in the vicinity of an understanding to enable the persons employed in them to perform they’re in healthy, congenial surroundings, and provided with amenities conductive to good health and high morale. It can also be classified as intramural and extramural. While intramural includes those welfare activities which ensures better quality of work like, scientific selection, trainee, good work environment, prevention of accidents, canteens, rest rooms, and refreshments etc.,. Extramural other welfare issues which also indirectly affect the quality of work life. Such issues cover, housing accommodation, medical services, recreation facilities, conveyance, social insurance scheme, provident fund benefits, pension, sickness, maternity benefits, school education for children etc.,. Industrial relations and Labour Welfare are two important areas governing employer–employee relations and benefits. For efficient management of an organization, it is essential to nurture healthy industrial relations and provide benefits to worker, both statutory and non-statutory. In India, we have several acts and legislations concerning these two areas. Many organizations, to derive motivational benefits provide welfare benefits beyond what are statutorily required.